Higher Education Students’ Experiences of Game-Based Learning - Fostering and Hampering Aspects in Virtual Teamwork - Syynimaa, Kirsi; Lainema, Kirsi; Lainema, Timo (ISTES Organization, 2026)
The application of digital game-based learning (GBL) methods has lately received more attention in higher education (HE). An extensive body of previous investigations has recognised the potential of instructional games to advance the learning of appropriate work life skills. However, there seems to be a lack of understanding in the current literature regarding the students’ views towards meaningful ways to collaborate in virtual teams during educational activities. The current study is contextualised by a business simulation game and examines university students' experiences through working collaboratively in multi-site teams. In that context, the focus is on the fostering and hampering aspects of virtual collaboration as experienced by the students during the simulation sessions. The study was executed among 66 undergraduate university students in Finland. The data were collected from the students' reflection papers and were then analysed using a qualitative content analysis approach. The evidence shows that students experienced fostering and hampering aspects in relation to communication, collaboration, organising, and technology during the simulated sessions. As these are all very typical to modern distributed collaborative work, we may conclude that the GBL course presented in this study provided students with opportunities to experience and rehearse collaborative virtual teamwork in an authentic work context. Our findings highlight the importance of allowing students to practice 21st century skills in an authentic, safe and stimulating environment. Simulation games provide a feasible context for doing so.